Pengaruh Pandemi COVID-19 Terhadap Motivasi Perilaku dan Metode Online Bagi Mahasiswa FK Undana - Sagita, Sidarta; E. Dedy , Maria Agnes; Artawan, I Made (Publikasi Indonesia, 2022)
Knowledge and attitudes about COVID-19 prevention behavior are very important, especially for health workers themselves, because currently there are health workers who have been confirmed positive for COVID-19. This causes several negative impacts that cause a lot of losses not only for the health workers but for families and students. Research on the effect of the COVID-19 pandemic on behavioral motivation and online methods for students has never been done, especially in East Nusa Tenggara (NTT), especially at Undana Medical Faculty. FK Undana is a public lecturer faculty in NTT. Therefore, researchers are interested in conducting research on